Foregut Duplication Cyst: An Unusual Presentation During Childhood - Hammoud, Ahmad (Medknow Publications & Media Pvt Ltd, 2012)
Congenital duplications can occur anywhere in the GIT, one third of all duplications are foregut duplications (esophagus, stomach, first and second part of duodenum). Respiratory symptoms are the most common symptoms in foregut duplications, most cases present with respiratory distress which may be present from birth, or symptoms may be insidious with cough, wheeze, or recurrent respiratory infections. We are presenting a 2-year-old boy presenting with cough and fever. Radiological investigation showed left mediastinal mass that was removed by excisional biopsy and revealed an esophageal cyst. Cough with or without fever could be rare presentations for esophageal cyst.